Eco-friendly synthesis and characterization of silver nanoparticles from an endemic plant and their antibacterial potency - A sustainable approach - R. Rajalakshmi; N. Mukesh Babu; A. Doss; R.P. Praveen Pole; T.P. Kumari Pushpa Rani; V. Mary Kensa (Chemistry of Inorganic Materials)
The biomass-assisted fabrication of green nanoparticles is in rise in recent years as it ensures environment compatibility and economically smartness. Now-a-days, the scientific world utilizing the abundantly available plant biomass to synthesize nanoparticles. The present study attempted the biofabrication of silver nanoparticles (Ag NPs) from the silver salt (silver nitrate) using the leaf extract from the plant, Jatropha maheshwarii. The functional groups attached, morphological features and the other qualities of J. maheshwarii mediated Ag NPs was done using the characterization techniques (spectroscopic and micrographic) like Fourier Transform Infra Red spectroscopy (FTIR), X-Ray Diffraction analysis (XRD), Energy Dispersive X-ray Analysis (EDXA), Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM). These analyses showed that the nanoparticles are spherical and flakes in shape and the XRD results indicated an average particle size of 25.98 ​nm. These nanoparticles were employed as an antibacterial agent on different bacteria such as Staphylococcus aureus, Bacillus thuringiensis, Escherichia coli, Pseudomonas aeruginosa and Salmonella typhi. The significant antibacterial activity exhibited against S. typhi (19 ​mm) at a concentration of 100 ​μg/ml. Furthermore, the mode of action of these bio-synthesized silver nanoparticles as an antibacterial agent was screened by the amount of reducing sugars and proteins leaked from the bacterial cells under study after treating with nanoparticles (leakage assay). These findings encourage the future development of these green nanoparticles as potential antibacterial drugs.